Case Study : Gardenia Bakeries (KL) Sdn. Bhd. / Wan Nurul Syafiqah Wan Pauzi - Wan Pauzi, Wan Nurul Syafiqah (2021)
In this case study, we will look at Gardenia Bakeries (KL) Sdn. Bhd. in the consumer markets including market segmentation and target setting. We will only concentrate on Gardenia Bakeries' products and marketing activities in Peninsular Malaysia. Aside from that, this case study focuses on the SWOT analysis that Gardenia developed this year, as well as its marketing environment, which is essential in implementing marketing activities. Furthermore, we will gain a better understanding of how Gardenia conducts its marketing activities in order to overcome the highly competitive environment and maintain its reputation as the dominant bakery or breads manufacturer among its competitors. The goal of conducting this analysis is to assist us in determining what techniques are actually implemented and how Gardenia manages to remain as the strongest brand in a highly competitive environment while also distinguishing itself from all other competitors, including SME bread producers in Malaysia, in terms of various strategies, plans, and ideas.